Pemberian Tepung Limbah Udang yang Difermentasi dalam Ransum Pakan Buatan Terhadap Laju Pertumbuhan, Rasio Konversi Pakan Dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) [The Given Fermentation The Prawn Waste Flour In Artificial Feed On Growth, Feed Convertion Ratio and Survival Rate Of Black Nile Tilapia (Oreochromis niloticus) ] - Agustono Agustono; Muhammad Hadi; Yudi Cahyoko (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
AbstractThe aim of this research was to find out optimum percentage of given fermentation the prawn waste flour in artificial feed on growth of black nile tilapia. The treatment of this research was giving fermentation the prawn waste flour in artificial feed i.e. 0%, 2,5%, 5%, 7,5%, 10%. Each treatment was repeated 4 times. Feed compositon was made of isoprotein. Fishes weight were about 6.1 – 6.8 g. Fishes were cultured with stocking rate 3 fish per 20 liter water and the fishes were reared for 40 days. Feed amount that consumed by fishes was measured every day to calculate feed conversion ratio. The calculation of fishes amount was done in beginning and end of research to count survival rate of fishes. Water quality was measured on beginning, middle and end of research. The design of this research was Completely Randomized Design. Data analysis used Analysis of Variance (ANOVA) to know the effect of the treatment and that difference among the treatment used Duncan's Multiple Range Test (DMRT). The result of the research showed that the highest growrth rate were attained on feed containing 10% of fermented prawn waste flour. The best feed convertion ratio were attained on feed containing 10% of fermented prawn waste flour.